2015
DOI: 10.1136/postgradmedj-2014-132987
|View full text |Cite
|
Sign up to set email alerts
|

Do questions help? The impact of audience response systems on medical student learning: a randomised controlled trial

Abstract: Embedding three ARS questions within a 30 min lecture increased students' knowledge immediately after the lecture and 2 weeks later. We hypothesise that this increase was due to forced information retrieval by students during the learning process, a form of the testing effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Other studies have shown there to be no impact of the use of audience response devices in long-term knowledge retention [28, 30]. Contrary to this, one recent randomised clinical trial assessing the impact of audience response devices on medical student learning did find that the devices, along with three embedded questions in a 30 min lecture, improved students’ knowledge immediately after the session and again two weeks later [15]. They speculated that this effect was due to forced information retrieval by the students brought on by the learning process [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown there to be no impact of the use of audience response devices in long-term knowledge retention [28, 30]. Contrary to this, one recent randomised clinical trial assessing the impact of audience response devices on medical student learning did find that the devices, along with three embedded questions in a 30 min lecture, improved students’ knowledge immediately after the session and again two weeks later [15]. They speculated that this effect was due to forced information retrieval by the students brought on by the learning process [15].…”
Section: Discussionmentioning
confidence: 99%
“…At this point the individual(s) delivering the session discuss the bar chart and explain why the answer options are correct or incorrect. Their application in the clinical teaching environment is also becoming more common and numerous studies have shown their use to be beneficial due to their ability to increase student engagement and to promote knowledge retention [1215]. …”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods other than didactic teaching is available and may be beneficial to improve the retention of information [48,49]. Using online surveys may also help to increase the number of attending dentists and thus stronger evidence can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Active learning is superior to lecture for learner retention. 3 If the groups that improved were given the webinar, this could account for their change. The difference may also be explained by confounding variables.…”
Section: Re: Clinical Decisions Made In Primary Care Clinics Before Amentioning
confidence: 99%